Super edge trimagic total labeling of generalized prism and web graphs. (2nd January 2016) - Regees, M.; Jayasekaran, C.
Abstract: An edge magic total labeling of a ( p, q ) graph is a bijection f : V ( G ) ∪ E ( G ) → 1, 2,  … , p + q such that for each edge xy ∈ E ( G ), the value of f ( x ) + f ( xy ) + f ( y ) is a constant k . If there exists three constants k 1, k 2 and k 3 such that f ( x ) + f ( xy ) + f ( y ) is either k 1 or k 2 or k 3, it is said to be an edge trimagic total labeling. In this paper we prove that the generalized Prism G = C m  P n′ the generalized web graph WB ( C m′ n ) and the generalized web graph without centre WB0 ( C m′ n ) are super edge trimagic total graphs